Have faith in your vocabulary. The role of the interpreter in the conquest of power, language and ideology in the New Spain - D'Amore, Anna Maria; Murillo Gallegos, Verónica del Carmen; Zimányi, Krisztina (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2016)
Crucial in the moments of initial contact and military conflict during the conquest, translation and interpreting continued to play a fundamental role throughout the 16th and 17th centuries in the New Spain. With evangelization both the means and end to control and conquest, the ideological conflict required the active participation of both translators and interpreters. Community interpreting in the context of conflict, colonization and evangelization in the region saw the collaboration of various actors/agents, and there is much speculation, if little reliable documentation, regarding their participation. This paper aims to analyse the role of interpreters and translators in the indoctrination of the local populations through a study of the document known as Los Coloquios de 1524, a text compiled fifty years after the actual conquest, that aspired to reconstruct the first contact with, and attempts at evangelization of, the indigenous population by Spanish Franciscan friars. Apparently under the supervision of the Franciscans, the role of indigenous Nahuatl speaking interpreters was paramount in the conceptualization -via Nahuatl- of Christianity in the New Spain, first interpreting indigenous religious and cultural practice and then adapting and reconstructing notions of Christianity for local consumption. Through the translation and interpretation of conflict between languages, religions and worldviews, changes in ideas, language and culture, and thus power, took place in the interstices and metaphorical spaces of negotiation.